High HIV and active tuberculosis prevalence and increased mortality risk in adults with symptoms of TB: a systematic review and meta‐analyses. Issue 7 (31st July 2018) - Nliwasa, Marriott; MacPherson, Peter; Gupta‐Wright, Ankur; Mwapasa, Mphatso; Horton, Katherine; Odland, Jon Ø; Flach, Clare; Corbett, Elizabeth L.
Abstract: Introduction: HIV and tuberculosis (TB) remain leading causes of preventable death in low‐ and middle‐income countries (LMICs). The World Health Organization (WHO) recommends HIV testing for all individuals with TB symptoms, but implementation has been suboptimal. We conducted a systematic literature review and meta‐analyses to estimate HIV and TB prevalence, and short‐term (two to six months) mortality, among adults with TB symptoms at community‐ and facility level. Methods: We searched Embase, Global Health and MEDLINE databases, and reviewed conference abstracts for studies reporting simultaneous HIV and TB screening of adults in LMICs published between January 2003 and December 2017. Meta‐analyses were performed to estimate prevalence of HIV, undiagnosed TB and mortality risk at different health system levels. Results: Sixty‐two studies including 260, 792 symptomatic adults were identified, mostly from Africa and Asia. Median HIV prevalence was 19.2% (IQR: 8.3% to 40.4%) at community level, 55.7% (IQR: 20.9% to 71.2%) at primary care level and 80.7% (IQR: 73.8% to 84.6%) at hospital level. Median TB prevalence was 6.9% (IQR: 3.3% to 8.4%) at community, 20.5% (IQR: 11.7% to 46.4%) at primary care and 36.4% (IQR: 22.9% to 40.9%) at hospital level. Median short‐term mortality was 22.6% (IQR: 15.6% to 27.7%) among inpatients, 3.1% (IQR: 1.2% to 4.2%) at primary care and 1.6% (95% CI: 0.45 to 4.13, n = 1 study) at community level. Conclusions: Adults with TB symptoms have extremely high prevalence of HIV infection, even when identified through community surveys. TB prevalence and mortality increased substantially at primary care and inpatient level respectively. Strategies to expand symptom‐based TB screening combined with HIV and TB testing for all symptomatic individuals should be of the highest priority for both disease programmes in LMICs with generalized HIV epidemics. Interventions to reduce short‐term mortality are urgently needed.